Convergence Theorems Based on the Shrinking Projection Method for Hemi-relatively Nonexpansive Mappings, Variational Inequalities and Equilibrium Problems: Zi-Ming Wang, Sun Young Cho, Yongfu Su - Team, Support (Thai Journal of Mathematics, 2017)
In this paper, hemi-relatively nonexpansive mappings, variational inequalities andequilibrium problems are considered based on a shrinking projectionmethod. Strong convergence of iterative sequences is obtained in a uniformly convex and uniformly smooth Banach space. As an application, the problem of finding zeros of maximal monotoneoperators is studied.